2010
DOI: 10.1097/jom.0b013e3181d46f0b
|View full text |Cite
|
Sign up to set email alerts
|

Second-Year Results of an Obesity Prevention Program at The Dow Chemical Company

Abstract: Objective Evaluate innovative, evidence-based approaches to organizational/supportive environmental interventions aimed at reducing the prevalence of obesity among Dow employees after two years of implementation. Methods A quasi-experimental study design compared outcomes for two levels of intervention intensity to a control group. Propensity scores were used to weight baseline differences between intervention and control subjects. Difference-in-differences methods and multi-level modeling were used to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 28 publications
1
63
2
Order By: Relevance
“…In an evaluation of a worksite obesity prevention program, Goetzel et al randomized worksites to one of three types of programs, each with different levels of promotion. 57 Reductions in BMI and cholesterol were only significant among the programs with higher levels promotion activities.…”
Section: Is More Always Better When It Comes To Workplace Wellness Prmentioning
confidence: 99%
“…In an evaluation of a worksite obesity prevention program, Goetzel et al randomized worksites to one of three types of programs, each with different levels of promotion. 57 Reductions in BMI and cholesterol were only significant among the programs with higher levels promotion activities.…”
Section: Is More Always Better When It Comes To Workplace Wellness Prmentioning
confidence: 99%
“…More recent studies have found pronounced improvements. Goetzel et al (2010) using a quasi-experimental research design, with two levels of intervention intensity and a control group found significant differences in blood pressure (systolic and diastolic) and cholesterol values while intervention participants maintained their weight and BMI compared to the control sight participants who gained 1.3 pounds and increased their BMI by 0.2 over two years.…”
Section: Additional Analysismentioning
confidence: 99%
“…Offering wellness programs may be an efficient strategy in promoting health and wellness (Dishman, Oldenburg, O'Neal, & Shephard, 1998;Engbers, van Poppel, Paw & van Mechelen, 2005;Goetzel et al, 2010;Proper et al, 2003). Although comprehensive efforts to lower the risk status of those in moderate or high-risk categories should be made, the needs of currently healthy workers must be addressed as well to avoid increases in risk status (Edington & Burton, 2003;Merrill & Sloan 2014;Musich et al, 2003).…”
Section: Organizational Wellness Programs -A Business Strategymentioning
confidence: 99%
See 2 more Smart Citations